Perbaikan Aspek Produksi, Manajemen dan Hukum Kelompok UMKM “Tuty Collections” - Saefullah, Encep; Mukhlis, Ahmad; Hifni, Mohammad (Universitas Nusantara PGRI Kediri, 2024)
The problems of the target partners of the